2017
DOI: 10.1038/srep44134
|View full text |Cite
|
Sign up to set email alerts
|

Size matters for in vitro gene delivery: investigating the relationships among complexation protocol, transfection medium, size and sedimentation

Abstract: Although branched and linear polyethylenimines (bPEIs and lPEIs) are gold standard transfectants, a systematic analysis of the effects of the preparation protocol of polyplexes and the composition of the transfection medium on their physicochemical behaviour and effectiveness in vitro have been much neglected, undermining in some way the identification of precise structure-function relationships. This work aimed to address these issues. bPEI/DNA and lPEI/DNA, prepared using two different modes of addition of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 37 publications
10
86
0
1
Order By: Relevance
“…Interestingly, polyplex formations in 150 mM NaCl showed small polyplexes with a low PDI for P(M n A m ) whereas for P(E n A m ) mostly aggregates larger than 700 nm with a high PDI could be detected (Table ). The influence of N/P ratio and transfection medium for l ‐PEI was recently shown and are in good accordance to our results …”
Section: Resultssupporting
confidence: 93%
“…Interestingly, polyplex formations in 150 mM NaCl showed small polyplexes with a low PDI for P(M n A m ) whereas for P(E n A m ) mostly aggregates larger than 700 nm with a high PDI could be detected (Table ). The influence of N/P ratio and transfection medium for l ‐PEI was recently shown and are in good accordance to our results …”
Section: Resultssupporting
confidence: 93%
“…The results also showed that with the addition of fresh CHOMACS CD medium up to 5 mL at 5 hpt, the unknown PEI inhibitory components of CHOMACS CD medium had a negligible effect on transfection efficiency. Consistent with this finding, most transfection events occurred within the first hour after transfection, when 80% of the pDNA/PEI polyplex is taken up by the cells [16,33]. Therefore, volumetric upscaling of the high cell density transfected culture through medium addition at 5 hpt decreased its cell density to extend the protein production time as showed in Supporting Information Figure S2.…”
Section: Screening Of High Cell Density Transfection Mediumsupporting
confidence: 74%
“…To guarantee appropriate biological performance and a successful transfection with the nanocomplexes, it is essential to evaluate their colloidal stability in the transfection medium. In this study, we used Opti-MEM™, as it is commonly used for transfection purposes in various cell lines [43,44]. Furthermore, we supplemented the medium with HEPES and mannitol, based on a recommendation for transfection with the commercially available CS-based transfection reagent, Novafect, from NovaMatrix ® (Sandvika, N).…”
Section: Supplemented Transfection Medium Stabilizes Nanocomplexes Bumentioning
confidence: 99%